Unresectable leiomyosarcoma of the inferior vena cava with right atrium tumor thrombus: when to deem this tumor inoperable? A case report and literature review - Castellanos, Luis D.; Tabbara, Marina M.; Livingstone, Alan S.; Salerno, Tomas A.; Gonzalez, Javier; Ciancio, Gaetano (Frontiers in Oncology, 2024)
Leiomyosarcomas (LMS) of the inferior vena cava (IVC) are a rare form of retroperitoneal malignancy and their venous extension to the right atrium is an even rarer event. These tumors pose a unique surgical challenge and often require a multidisciplinary team-based approach for their surgical treatment. We present a case of a 68-year-old male with primary LMS of the IVC with a tumor thrombus extending into the right atrium that was initially deemed inoperable. After extensive neoadjuvant chemo-radiation with minimal tumor effect, the patient underwent en-bloc surgical resection of the tumor along with removal of the infrarenal IVC and right kidney and adrenal without the need for cardiopulmonary bypass. This case demonstrates the successful management of a primary LMS of the IVC with right atrial extension using a multimodal approach of neoadjuvant chemo-radiation and en-bloc surgical resection without cardiopulmonary bypass. This strategy may offer a curative option for selected patients with these rare and aggressive tumors, improving their survival and quality of life.